Single Nucleotide Variation Analysis in 65 Candidate Genes for CNS Disorders in a Representative Sample of the European Population - Freudenberg-Hua, Yun; Freudenberg, Jan; Kluck, Nadine; Cichon, Sven; Propping, Peter; Nöthen, Markus M. (Genome Research, 2003)
The detailed investigation of variation in functionally important regions of the human genome is expected to promote understanding of genetically complex diseases. We resequenced 65 candidate genes for CNS disorders in an average of 85 European individuals. The minor allele frequency (MAF), an indicator of weak purifying selection, was lowest in radical amino acid alterations, whereas similar MAF was observed for synonymous variants and conservative amino acid alterations. In noncoding sequences, variants located in CpG islands tended to have a lower MAF than those outside CpG islands. The transition/transversion ratio was increased among both synonymous and conservative variants compared with noncoding variants. Conversely, the transition/transversion ratio was lowest among radical amino acid alterations. Furthermore, among nonsynonymous variants, transversions displayed lower MAF than did transitions. This suggests that transversions are associated with functionally important amino acid alterations. By comparing our data with public SNP databases, we found that variants with lower allele frequency are underrepresented in these databases. Therefore, radical variants obtain distinctively lower database coverage. However, those variants appear to be under weak purifying selection and thus could play a role in the etiology of genetically complex diseases.
10.1101/gr.1299703